1993
DOI: 10.1366/0003702934067928
|View full text |Cite
|
Sign up to set email alerts
|

Multivariate Determination of Glucose in Whole Blood Using Partial Least-Squares and Artificial Neural Networks Based on Mid-Infrared Spectroscopy

Abstract: The infrared (IR) spectra of whole blood EDTA samples, in the range between 1500 and 750 cm−1, obtained from the patient population of a general hospital, were used to compare different multivariate calibration techniques for quantitative glucose determination. Ninety-six spectra of whole undiluted blood samples with glucose concentration ranging between 44 and 291 mg/dL were used to create calibration models based on a combination of partial least-squares (PLS) and artificial neural network (ANN) methods. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
49
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(51 citation statements)
references
References 31 publications
2
49
0
Order By: Relevance
“…Mid-IR investigations [26][27][28][29][30][31][32] have typically yielded assays with standard errors of prediction of approximately 0.6 mmol/L, independent of the experimental details (e.g. ATR vs. transmission, liquid vs. dry film).…”
Section: Whole Bloodmentioning
confidence: 99%
“…Mid-IR investigations [26][27][28][29][30][31][32] have typically yielded assays with standard errors of prediction of approximately 0.6 mmol/L, independent of the experimental details (e.g. ATR vs. transmission, liquid vs. dry film).…”
Section: Whole Bloodmentioning
confidence: 99%
“…One solution is to use attenuated total reflection (ATR) spectroscopy rather than transmission measurements. A series of publications from Heise and co-workers has demonstrated that this approach can provide the basis to quantify native plasma, 3,4 whole blood, 5,6 and urine 7 constituents. A second approach is to eliminate the water absorptions by simply drying the specimens, and carrying out transmission measurements on the dry films.…”
Section: Vibrational Spectroscopy For the Analysis Of Biological Fluimentioning
confidence: 99%
“…37 A different approach, which is able to model nonlinearities explicitly, is the application of neural networks. 33,38 As in other multivariate methods, calibration by ''learning'' is essential, but such an approach tends to be more susceptible to overfitting, and more difficult to handle and interpret than the linear approaches discussed before.…”
Section: Chemometrics For Quantitative Spectrum Evaluationmentioning
confidence: 99%